Characterization of the species of Pythium associated with corn seedlings in Delaware - Bickel, John (Plant disease, 2024)
Corn (Zea mays L.) is the top grain crop by hectares grown in Delaware (DE). Increased pre- and post-emergence damping-off in corn caused by Pythium species have been observed in recent seasons. To date, no characterization studies have been performed to understand Pythium species diversity in DE. Symptomatic corn seedlings were collected from 33 fields across DE in 2019 and 2020. Isolates were obtained from infected root tissues and identified by molecular sequencing. In total, 14 species were recovered: P. aristosporum, P. arrhenomanes, P. attrantheridium, P. catenulatum, P. dissotocum, P. graminicola, P. inflatum, P. irregulare, P. oligandrum, P. periplocum, P.spinosum, P. sylvaticum, P. tardicrescens, and P. torulosum. The dominant species recovered was P. graminicola, accounting for 66% of the isolates. Five species were screened for fungicide sensitivity to calculate the EC50 of mefenoxam, ethaboxam, and picarbutrazox which are the most commonly used active ingredients to manage species of Pythium in corn seed treatment packages. All species tested were sensitive to mefenoxam and picarbutrazox. For ethaboxam, P. torulosum was the only species with an EC50 value > 10 µg ml 1. Ten species were screened for fungicide sensitivity to mefenoxam, ethaboxam, or picarbutrazox at 18, 21, and 25ºC. As temperatures increased, percent inhibition was reduced in 40, 70, and 80% of the species screened for sensitivity to ethaboxam, picarbutrazox, and mefenoxam, respectively. Nine of these species were screened for isolate aggressiveness in greenhouse panels to examine impact on emergence, shoot height, shoot weight, and root weight. While all species were recovered from inoculated roots, P. arrhenomanes, P. attrantheridium, P. spinosum, and P. sylvaticum had the greatest root weight reduction